Assessing the value of growth option synergies from business combinations and testing for goodwill impairment a real options perspectives. - Baldi, Francesco
Vol. 21 no. 4 : pp. 115-124 Fa 09
Keywords: Periodical; FASB statements -- SFAS 142.; Business combinations